2003
DOI: 10.1161/01.res.0000094745.28948.4d
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Regulation, and Function of Mammalian Membrane Guanylyl Cyclase Receptors, With a Focus on Guanylyl Cyclase-A

Abstract: Abstract-Besides soluble guanylyl cyclase (GC), the receptor for NO, there are at least seven plasma membrane enzymes that synthesize the second-messenger cGMP. All membrane GCs (GC-A through GC-G) share a basic topology, which consists of an extracellular ligand binding domain, a short transmembrane region, and an intracellular domain that contains the catalytic (GC) region. Although the presence of the extracellular domain suggests that all these enzymes function as receptors, specific ligands have been iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
161
1
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(172 citation statements)
references
References 131 publications
2
161
1
4
Order By: Relevance
“…73,74 Ligand-induced NPR-A and NPR-B activation generates cGMP in target cells which in turn activates signal transduction elements such as low-and high-affinity cGMP-dependent protein kinases (PKGs). 75 NPR-C, which has a short cytoplasmic domain without GC activity, influences plasma natriuretic peptide levels and ANP half-life and acts systemically to control natriuresis and blood pressure. Although some mechanisms of action mediated by NPR-C remain unclear, it is recognized that NPR-C acts as a clearance receptor which allows the activity of the NP system to be tailored to specific local needs.…”
Section: Natriuretic Peptide Receptorsmentioning
confidence: 99%
“…73,74 Ligand-induced NPR-A and NPR-B activation generates cGMP in target cells which in turn activates signal transduction elements such as low-and high-affinity cGMP-dependent protein kinases (PKGs). 75 NPR-C, which has a short cytoplasmic domain without GC activity, influences plasma natriuretic peptide levels and ANP half-life and acts systemically to control natriuresis and blood pressure. Although some mechanisms of action mediated by NPR-C remain unclear, it is recognized that NPR-C acts as a clearance receptor which allows the activity of the NP system to be tailored to specific local needs.…”
Section: Natriuretic Peptide Receptorsmentioning
confidence: 99%
“…5,6 Recent pharmacologic studies suggested that soluble GC are involved in a chronic model of glomerulonephritis 7,8 ; however, little is known about the role of receptor GC in renal diseases.…”
mentioning
confidence: 99%
“…In mammals, seven isoforms of receptor GC have been identified: GC-A through GC-G. 5,6 GC-A and GC-B function as receptors for atrial natriuretic peptide (ANP) and B-type natriuretic peptide, and GC-C mediates the effects of guanylin and uroguanylin on intestinal electrolyte and water transport. 5,6 Endogenous ligands for GC-D, -E, -F, or -G have yet to be identified; therefore, these receptors remain as orphans.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…L'activation des MAP-kinases est associée à une augmentation des taux intracellulaires d'AMPc et à une phosphorylation de la sérine (Ser 600 ) de la LHS [8,9]. [11]. Dans un premier temps, nous avons découvert que ces peptides exerçaient une action spéci-fique sur la lipolyse in vitro, puis nous avons mis en évi-dence un effet sur la mobilisation des lipides in vivo.…”
Section: Les Voies Classiques De Régulation De La Lipolyse Chez L'hommeunclassified